Clear Cell Sarcoma in an Elderly Man - Dayangku Norlida, Awang Ojep; Vernon Tan, Sze Yuen; Than Than, Aye; Mohammad Zulkarnaen, Ahmad Narihan (2025)
Clear Cell Sarcoma of Soft Tissue (CCSST) is a rare, aggressive tumour with melanocytic differentiation, often referred to as “malignant melanoma of soft parts.” First described by Enzinger in 1965, it accounts for < 1% of soft tissue sarcomas and characterised by an EWSR1–ATF1 gene fusion resulting from a t(12;22) translocation. CCSST typically affects young adults (20–40 years) and arises deep in the extremities, often near tendons or aponeuroses. Its close histological and immunohistochemical resemblance to melanoma makes diagnosis challenging, particularly in atypical sites or older patients. Molecular confirmation using FISH or next-generation sequencing is now essential. Surgical resection remains the primary treatment for localised disease, though options for metastatic CCSST are limited. This case aims to raise awareness that CCSST can occur outside its classical age range and anatomical sites, and should be considered in the differential diagnosis of deep soft tissue tumours, even in elderly patients.